Analysis of seroprevalence data on Hepatitis E virus and Toxoplasma gondii in wild ungulates for the assessment of human exposure to zoonotic meat-borne pathogens. (February 2022) - Crotta, Matteo; Pellicioli, Luca; Gaffuri, Alessandra; Trogu, Tiziana; Formenti, Nicoletta; Tranquillo, Vito; Luzzago, Camilla; Ferrari, Nicola; Lanfranchi, Paolo
Abstract: Seroprevalence data for Toxoplasma gondii and Hepatitis E virus (HEV) in wild boar ( Sus scrofa), roe deer ( Capreolus capreolus), red deer (Cervus elaphus), mouflon ( Ovis aries/musimon ) and chamois (Rupicapra rupicapra) hunted/culled in northern Italy were used to fit seroprevalence distributions describing the exposure and co-exposure of the species to the two pathogens. The higher proportion of T. gondii and HEV seropositive animals was observed in wild boars with point estimate seroprevalence of 49% (N = 331) and 15% (N = 326) respectively. Data allowed comparisons by area (pre-Alpine Vs Alpine environment) for roe deer, red deer and mouflons. Contrasts between the distributions describing the uncertainty in seroprevalence suggest roe deer, red deer and mouflons have higher probability of being seropositive to T. gondii in pre-Alps. When considering HEV, few seropositive animals were detected and contrasts were symmetrically centred to zero for roe deer and red deer; mouflons shown higher probability of being seropositive in Alpine environment. HEV seropositive animals also included chamois (P = 5.1%, N = 97) in the Alpine districts, confirming circulation of HEV in remote areas. Evidence of HEV and T. gondii co-exposure was limited except for wild boars where it was observed in 30 samples representing 60% of the overall HEV-positive samples. Seroprevalence data of single infection and co-infection are extremely useful to investigate circulation of zoonotic pathogens in wild animals and estimate the foodborne risk of human exposure, however, these type of data do not directly translate into the presence/absence of the pathogen in seropositive and seronegative animals. At benefit of future development of quantitative risk assessments aiming at estimating the risk of human infection/co-infection via consumption of game meat, we developed and made available an online application that allows estimating the probability of the pathogen(s) being present as a function of seroprevalence data. Highlights: Co-exposure to T. gondii and HEV was explored in five game species. Seroprevalence data suggest wild boar meat poses the higher food safety risk to consumers. A method for use of seroprevalence data in risk assessment models is proposed.